EPDR1, Which Is Negatively Regulated by miR-429, Suppresses Epithelial Ovarian Cancer Progression via PI3K/AKT Signaling Pathway - Zhao, Zhendan; Wang, Zhiling; Wang, Pengling; Liu, Shujie; Li, Yingwei; Yang, Xingsheng (Frontiers in Oncology, 2021)
Epithelial ovarian cancer (EOC) is the main subtype of ovarian cancer. In this study, we found that Ependymin-related 1 (EPDR1) was significantly downregulated in EOC tissues and low EPDR1 expression was associated with International Federation of Gynecology and Obstetrics (FIGO) stage, metastasis and poor prognosis. We confirmed that EPDR1 overexpression dramatically inhibited EOC cells proliferation, migration and invasion in vitro and in vivo. Mechanistically, EPDR1 suppressed EOC tumorigenesis and progression, at least in part, through inhibiting PI3K/AKT pathway. Furthermore, the expression and function were regulated by miR-429, as demonstrated by luciferase reporter assays and rescue experiments. In conclusion, our study demonstrated that EPDR1, negatively regulated by miR-429, played an important role in EOC development via PI3K/AKT pathway. The miR-429/EPDR1 axis might provide promising therapeutic targets for individualized treatment of EOC patients in future.